Sistema para el control de producción de la fábrica textilera “Súper Pato” en el cantón La Maná - Luna Giler, Laura Roxana (2012)
The present investigation, consistent in the elaboration of a system for the production control, it was developed in the factory textilera Súper Pato of the cantón La Mana, county of Cotopaxi, with the purpose of automating the processes in the making area, for him which they thought about some objectives; by means of the analysis and flow of information that he/she was carried out in the factory, the imperious necessity was determined of having an automated system, he/she was carried out by means of an exhaustive study and he/she was proven that they take its registrations and information with respect to the control of production in an inadequate way. This system has been executed using the tools SQL Server, the structured consultation language (SQL) it is a normalized database language, used by the different motors of databases and design to carry out certain operations on the data or envelope the structure of the same ones. The application was developed in the language of programming Microsoft visual Csharp C #, it is a programming language designed to create a wide range of applications that you/they are executed in NET Framework, it is simple effective, with type security and guided to object. With their diverse innovations, C #it allows to develop applications quickly and it maintains the expresividad and distinction of the type languages C, an editor of complete code admits, project designers' insoles, assistants for code, an effective and easy purifier of using. In this system they were carried out the following investigations; of field, proyectiva and bibliographical, by means of surveys and interviews, as well as the analytic, synthetic, deductive and inductive methods. The system allows to carry out the following processes: to configure permission to enter the system like users, to enter, to keep to modify and to print employees' data, clients, suppliers, to register purchases (matter prevails), it works for orders, to show production reports, making state for order, remission guide, kardex etc. The implementation of the system will imply an organizational change, he/she won't only benefit to the production area, but he/she will also help to the administration when allowing to improve the production process, causing a direct impact in the organization of the company. It is feasible to carry out the automation in the area of production of the factory textilrera Súper Pato, because it has the proprietor's opening, administrator and personnel of the company; facilitating the access to the information to carry out an analysis in wide form of the necessary requirements for the development of the application.